The s(quad) model, a pattern approach for understanding the individual and their social network relations: application to loneliness - Ybarra, Oscar; Chan, Todd (Frontiers in Social Psychology, 2023)
The present research presents a model of how individuals relate to their personal social networks (i.e., spouse, children, other family, friends) by considering the degree to which the individual's needs for communion and agency are satisfied by these relations. The model proposes four prototypical configurations of the individual and their social network, which reflect different combinations of the high and low poles of communion and agency. The squad model is then applied to loneliness, an outcome the literature has considered predominantly from the perspective of deficits in the communion and relatedness domain with little attention paid to people's need for agency. Clustering analyses showed that people's networks can be characterized as proposed by the squad model, but also that loneliness varies as a function of both the level of communion and agency represented by each prototype. The findings thus contribute to our understanding of loneliness, but the framework is much broader and can be applied to varied outcomes. The model also has several implications for research on social networks as well as models of relationship processes.